With a Little Help From my Friends: Benefits and Challenges of Using Peer Review to Assist Journalism Students’ Learning - Mandow, Nikki (Auckland University of Technology, 2014)
Abstract Peer learning has become a well-used (and well-researched) learning strategy for tertiary students in disciplines as far apart as physics, music, tourism, dental hygiene and outdoor education. However, while there is anecdotal evidence peer learning is used in some journalism schools, there is almost no academic literature to answer the basic questions: how, when, why, where and who—and importantly, does it help journalism students learn? AUT University introduced peer review (students giving feedback on each other’s weekly news stories) into journalism classes in 2008. This action research study used questionnaires and collaborative group meetings to gather the views of third year News Reporting students and their tutors on the benefits of peer review to student learning, and the challenges of the process. The study found the students saw benefits arising in two separate areas: those from giving feedback, and those from receiving it. Initially, before the feedback took place, they envisaged more benefits arising from the latter, but this changed when they carried out the reviews, with reviewing seen as the most beneficial. This reflects findings in literature (Falchikov, 2007; Topping, 2009) about the benefits for the ‘teacher’ in reciprocal peer learning, but also reflects students’ perceived frustrations from the process, and from their classmates’ engagement in it. The study concluded there is good reason to believe journalism students can benefit from peer review. However there is a risk with journalism students that the active process of ‘peer reviewing’ (the giving of feedback on news stories), be confused with ‘peer editing’ (the more passive journalistic activity where editors make changes to reporters’ stories). While students wanted their peers to point out grammar and punctuation errors before their stories were seen by their tutor, there is the risk that such directive or superficial feedback (Cho & MacArthur, 2010; Hattie & Timperley, 2007) reduces the benefits to student learning; it may even hinder learning in some cases. The study also found participants believed preparation, training, modelling and monitoring to be crucial parts of the peer review process. Moreover, without the opportunity to discuss the feedback with each other, potential benefits of peer review could be lost. There are also additional benefits for students when they also discuss with their peers their learning from the peer review process itself. The importance of the structure of the peer review process means that while on the surface, peer review might appear to exclude the tutors, in fact their role is critical. When faced with challenges to the process, the study found many students default to the traditional, passive: ‘teacher, sort this out’ model. However, this research identified the role of the teacher in peer review as someone there to scaffold the student through the process of arriving at learning—not through the learning itself.
Keywords: Peer review; Journalism; Education; AUT University